Katodinium glaucum (Dinophyceae) revisited: proposal of new genus, family and order based on ultrastructure and phylogeny. Issue 2 (1st March 2016) - Boutrup, Pernille Vængebjerg; Moestrup, Øjvind; Tillmann, Urban; Daugbjerg, Niels
Abstract: Since its description in 1917, the taxonomy of Katodinium glaucum, a cosmopolitan heterotrophic marine dinoflagellate, has been in a state of flux. We added to this by arguing that Kat. glaucum is synonymous with both Amphidinium extensum and Gymnodinium vestifici . We presented a brief historical account of its shifting positions in Katodinium and Gyrodinium and a comparison with Gym. vestifici and A. extensum . The conclusions from our experimental work on a Kat. glaucum culture were based on both pheno- and genotypic characters obtained by light and electron microscopy and DNA sequencing. A nuclear-encoded large-subunit rDNA-based phylogeny revealed that Kat. glaucum and species of Torodinium are closely related and form a highly supported monophyletic lineage. The ultrastructural examination showed the apical structure complex of Kat. glaucum to comprise three rows of amphiesmal vesicles located beneath the cap-like projection on the anterior part of the cell. Torodinium, in comparison, possessed a counterclockwise spiral apical structure complex positioned on top of its bill-like apical projection. Species of both genera were longitudinally striated. The type species of Katodinium, Kat. nieuportense, was illustrated without any apical structures and without longitudinal striations, and because both morphological and molecular analysis also rejected relationship to Amphidinium, Gymnodinium and Gyrodinium, we proposed to erect a new genus for this species, Kapelodinium gen. nov . As the species name vestifici had priority over glaucum, the new name for the species was Kapelodinium vestifici comb. nov . To accommodate for the distinct difference in morphology of the apical structure complex in Torodinium and Kapelodinium, we further proposed two new monotypic families, Torodiniaceae fam. nov . and Kapelodiniaceae fam. nov . of the order Torodiniales ord. nov ., which in the molecular trees was not closely related to other dinoflagellates. The ultrastructural study of Kap. vestifici gen. & comb. nov . also revealed a number of characteristic features, such as a novel lip-like suture within the sulcus, cross-striated filaments beneath the apical projection and atypical nuclear chambers with pores towards both the nucleoplasm and the cytoplasm.